Activation of the calcium-sensing receptor in human valvular interstitial cells promotes calcification. (April 2019) - Issa, Hawraa; Hénaut, Lucie; Abdallah, Jeanne Bou; Boudot, Cédric; Lenglet, Gaëlle; Avondo, Carine; Ibrik, Aida; Caus, Thierry; Brazier, Michel; Mentaverri, Romuald; Zibara, Kazem; Kamel, Saïd
Abstract: Introduction and aims: Calcific aortic valve disease (CAVD) is the most common heart valve disease in western countries. It has been reported that activation of the calcium-sensing receptor(CaSR) expressed by vascular smooth muscle cells prevents vascular calcification. However, to date, the CaSR's expression and function in cardiac valves have not been studied. The present study sought to evaluate the presence of the CaSR within human valvular interstitial cells (hVICs), assess the CaSR's functionality, and ascertain its involvement in hVIC calcification. Methods and results: Data from Western blot, flow cytometry and immunocytochemistry experiments demonstrated that primary hVICs express the CaSR. The receptor was functional, since the incubation of hVICs with the calcimimetic R-568 significantly increased Ca 2+ -induced ERK1/2 phosphorylation, and exposure to the calcilytic NPS2143 reduced ERK1/2 activation. A reduction in endogenous CaSR expression by hVICs (using siRNA) was associated with significantly lower levels of Ca 2+ -induced mineralization (quantified using Alizarin Red staining). Similar data were obtained after the pharmacological inhibition of CaSR activity by the calcilytic NPS2143. In contrast, overexpression of a functional CaSR amplified Ca 2+ -induced calcification. Pharmacological activation of the CaSR with the calcimimetic R-568 showed similar effects. CaSR's procalcific properties are associated with increased osteogenic transition (as characterized by elevated mRNA expression of bone morphogenetic protein 2 and osterix), and reduced the expression of the calcification inhibitor osteopontin. Histological analysis of 12 human aortic tricuspid valves showed that CaSR expression was greater in calcified areas than in non-calcified areas. These data were confirmed by Western blots. Conclusions: To the best of our knowledge, this study is the first to have demonstrated that hVICs express a functional CaSR. Taken as a whole, our data suggest that activation of the CaSR expressed by hVICs might be a key promoter of CAVD progression. Highlights: Human valvular interstitial cells (hVICs) express the calcium-sensing receptor (CaSR) CaSR activation promoted the mineralization and osteogenic transition of hVICs. CaSR activation reduced the expression of the calcification inhibitor osteopontin. In hVICs, the CaSR might be a key promoter of calcific aortic valve disease progression